Results of teaching mathematics in a subject-based digital educational environment - Elvira Z. Galimullina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper presents the results of teaching mathematics to schoolchildren in a subject-based digital educational environment built according to the model proposed by the author. The aim of the study is to experimentally verify the effectiveness of the process of teaching mathematics to schoolchildren in a subject-based digital educational environment. The study required the use of a whole range of methods, such as observation, questioning, interpretation, tabular presentation of empirical data and their processing, static data processing and comparative analysis of the results. Two groups of students participated in the pedagogical experiment: the first group was an experimental group that studied mathematics in a subject-based digital educational environment, the second group was students who studied mathematics in a traditional form. In this study, the assumption was tested that the students of the experimental group show on average the same result of knowledge as the control group. To determine the absence of differences between the two experimental distributions, the students t-test was used. As a result, an alternative hypothesis was adopted that the students of the experimental group showed on average a higher level of knowledge than the participants of the control group. Therefore, it is possible to draw a conclusion about the effectiveness of the learning process based on the subject digital educational environment built according to the model proposed by the author.